Application of POET model to investigate agricultural water conflict in Iran - Bijani, Masoud; Hayati, Dariush; Fallah Haghighi, Negin; Valizadeh, Naser (Frontiers in Water, 2022)
Water conflicts might be a serious threat for the life quality of stakeholders and also an obstacle on the way of human and environmental development. Obviously, the environment could be affected by such conflicts. The purpose of this study was to investigate the agricultural water conflicts through a human ecological perspective using POET model and SWOT analysis. A descriptive mixed method including two surveys and semi-structured interviews was fulfilled as a research method. The study was conducted in Doroodzan dam irrigation network in Fars Province, Iran. The statistical population of this study included two groups of farmers and regional water experts; besides, the research tools included two questionnaires and semi-structured interviews. SWOT findings revealed that the best strategies reducing and controlling agricultural water conflict, and also maintaining and enhancing the environmental sustainability, are adaptation of participatory water management approaches, formation and strengthening of water user associations, and conformity of irrigation technologies with farmers' circumstances.